Some determinants of the innovation propensity of mexican products: The effect of R&D expenditures and knowledge spillovers - Méndez Delgado, Alba Verónica (Estudios Económicos de El Colegio de México, 2018)
This paper estimates the intensity of R&D expenditure, and is related to the propensity to innovate in the Mexico’s manufacturing firms. Moreover, the direct effect of knowledge spillovers over innovations is analyzed. The empirical analysis provides evidence that agreements with educational institutions and public financing has a positive effect over R&D expenditure and innovations. This paper concludes that the spillovers is relevant as they have a positive effect on the innovations; and the results show that excluding the spillovers from the analysis would generate an overestimation of R&D expenditure in innovations.